1985
DOI: 10.1002/cber.19851180531
|View full text |Cite
|
Sign up to set email alerts
|

The molecular and electronic structure of dipiperidinosquaraine

Abstract: Dipiperidinosquaraine (9) crystallizes in the orthorhombic system, space group Pnab, with four molecules in a cell of dimensions a = 7.1798(9), b = 9.5362(8), and c = 18.788(2) A. The molecule is located over a center of symmetry, so the four-membered ring (C -C = 1.456(1) A av) is exactly planar; the nitrogen and oxygen atoms are nearly coplanar with the ring, with C -0 = 1.2396(7) and C -N = 1.3112(7) A. Both experimental and theoretical evidence indicates the presence of considerable C -N and C -0 n-bonding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Support for this description can also be gleaned from work on amino squaraines. Both experimental and theoretical studies (9,10) on a related series of aminosquaraine compounds (7 and 8) indicated that these compounds experience considerable C-N a-bonding between the central four-membered ring and the amino substituents, supporting the MNDO evidence presented for aryl squaraines.…”
mentioning
confidence: 59%
“…Support for this description can also be gleaned from work on amino squaraines. Both experimental and theoretical studies (9,10) on a related series of aminosquaraine compounds (7 and 8) indicated that these compounds experience considerable C-N a-bonding between the central four-membered ring and the amino substituents, supporting the MNDO evidence presented for aryl squaraines.…”
mentioning
confidence: 59%
“…These bonding characteristics can be explained by the p‐π conjugation of the lone pairs on O(1) and N(2) and the carbon p orbital 10. Like previously reported squaraines, the C atoms in the four‐membered ring in 2 are all sp 2 hybridized 2b. Delocalization of the electrons is believed to exist, and this accounts for the longer C(1)−C(4A) double bond [1.428(3) Å].…”
Section: Resultsmentioning
confidence: 63%
“…There are some noticeable differences in the structure of the squaraine ligands in complex 2 compared to those reported previously 2b,2c,6. The C(2)−N(1) bond length of 1.281(3) Å is typical of a C=N double bond (1.273 Å in CH 2 =NH8).…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations